Edukasi Pencegahan Hipertensi dan Pelatihan Pengolahan Sampah Organik sebagai Strategi Peningkatan Kesehatan dan Kualitas Lingkungan Masyarakat di Kelurahan Toronipa - Purnamasari, Anisa; Nofitasari, Ari; Apriawal, Jabbal; Andriani, Rina; Saranani, Selpirahmawati (Karya Kesehatan Journal of Community Engagement, 2025)
Community Service Activity (PKM) was carried out in Kelurahan Toronipa with the aim of enhancing the community’s knowledge and skills in the areas of health and environmental management. The main issues identified were the high prevalence of hypertension and the low public awareness regarding proper household waste management. This program was implemented by supervising lecturers and thematic KKN (Kuliah Kerja Nyata) students from various study programs (Sanitation, Nursing, Pharmacy, Psychology and Public Health) using an educational and participatory approach. The activities conducted included waste management education, stress management training for individuals with hypertension, blood pressure and blood sugar screening, and health education on non-communicable diseases such as hypertension and diabetes mellitus. The results showed that 48 participants attended the waste management education session, with 30 successfully practicing Takakura composting and 15 individuals bringing ecobricks home. Stress management training was attended by 32 participants, 25 of whom stated that the relaxation techniques were easy to implement at home. A total of 61 individuals participated in the health screening, which identified 18 with high blood pressure and 7 with elevated blood sugar levels, all of whom were referred for further medical evaluation. The education session on non-communicable diseases was attended by 55 participants, with 90% able to mention at least two risk factors for hypertension and diabetes. These findings demonstrate that educational interventions are effective in increasing community awareness of healthy lifestyles and environmental management. It is recommended that this program be continued through collaboration with local health institutions and government authorities to achieve broader and more sustainable impact.